PEMBERDAYAAN PEREMPUAN DAN LANSIA MELALUI WORKSHOP SANGGUL TRADISIONAL DAN SENAM SEHAT DI DESA JAGAPATI, KECAMATAN ABIANSEMAL - Made Ari Nohan Tara; I Komang Adi Palgunadi; Ni Luh Gede Epan Sintia Dewi; Ni wayan saba astuti; I Made Indra Sanjaya; I Dewa Gde Sangging Budiartana; Roni Kanata; Egiregius Harjo; I Gede Surya Arta Wiguna; Ni Putu Ayu Trisnayanti; Ni Made Dwi Handayani; Venansius Andrino woi; I Kadek Oke Prawira Wibawa (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
The Thematic Community Service Program (KKN) conducted by Group 8 of Universitas PGRI Mahadewa Indonesia in Jagapati Village, Abiansemal District, aimed to empower women and the elderly through culturally based activities. The core initiatives included a traditional Balinese hair bun (sanggul) workshop for local women and wellness exercises for senior citizens, designed to enhance practical skills, physical fitness, and social engagement. The sanggul workshop provided an opportunity for women to learn traditional makeup techniques that could be applied in ceremonial contexts or developed into small-scale entrepreneurial ventures. Meanwhile, the wellness sessions for the elderly served as a platform to maintain physical and mental health while fostering social connection. The program employed a participatory method involving observation, hands-on training, and evaluation. Results showed strong participant engagement and increased motivation for community involvement. This initiative reflects a meaningful collaboration between students and local residents in building a healthy, empowered, and culturally rooted village.